Digital Humanities come risorsa per i translation studies - Gallitelli, Eleonora (Status Quaestionis, 2017)
In Anglo-Saxon countries the digital humanities (known as “informatica umanistica” or “umanistica digitale” in Italian) enjoy a good reputation among scholars and researchers of linguistics and translation studies. In Italy, on the contrary, this area of research is still looked on with some suspicion, especially when its methodologies are applied to literary texts, this despite the fact that software-based corpus linguistics studies have often given interesting results indicating trends of various kinds. This paper presents as an example one of the many possible applications of digital humanities, a semi-automatic analysis based on a corpus of Italian novels and novels translated into Italian from English. The study sought to establish whether, in different periods of recent Italian history (from national unification to the present day), “translated literature” (Even-Zohar [1978] 1990) has shown peculiar and characteristic traits when compared to fictional texts written directly in Italian. A short description of the main phases of this study will be followed by a reflection on the perspectives opened by digital humanities, which can be seen as a useful tool to get to the heart of language change and dismantle the most enduring stereotypes regarding language and translation.